Note from the editor: Ecologizing economic sociology - Leon Wansleben (economic sociology. perspectives and conversations, 2024)
Economic activities force earth systems to undergo dramatic changes, while some ecosystems collapse. In consequence, conditions for economic activities change, sometimes rapidly and sometimes in slow motion. Under these circumstances, economic sociologists can no longer afford to study selected markets and firms as if they existed in some immaterial social space rather than on planet earth. Ecologizing economic sociology is thus not some niche project occupying the small area at the intersecting circles of economic and environmental sociology, but means going to the heart of economic sociology itself in order to rethink its defining categories and concepts. I am happy that the contributors to this issue have agreed to take up the challenge.
Keywords: 300